2014
DOI: 10.1097/med.0000000000000027
|View full text |Cite
|
Sign up to set email alerts
|

Update on neonatal hypoglycemia

Abstract: Purpose of Review Neonatal hypoglycemia is one of the most common biochemical abnormalities encountered in the newborn. However, controversy remains surrounding its definition and management especially in asymptomatic patients. Recent Findings New information has been published that describes the incidence and timing of low glucose concentrations in the groups most at risk for asymptomatic neonatal hypoglycemia. Furthermore, one large prospective study failed to find an association between repetitive low glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
15

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 63 publications
0
30
0
15
Order By: Relevance
“…3 This provides a possible rationale to the poor performance of previous self-testing glucometers in neonatal care. 5,6 A tighter accuracy requirement, as proposed in current study (±10 mg/dl), is thus warranted to address the specificity of neonatal blood for effective diabetes management and glycemic control. …”
Section: Letter To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…3 This provides a possible rationale to the poor performance of previous self-testing glucometers in neonatal care. 5,6 A tighter accuracy requirement, as proposed in current study (±10 mg/dl), is thus warranted to address the specificity of neonatal blood for effective diabetes management and glycemic control. …”
Section: Letter To the Editormentioning
confidence: 99%
“…2,4 This cutoff value serves as a useful guideline for clinicians to take appropriate actions, including retesting and continued monitoring of blood glucose, and providing glucose source in oral feeding or intravenous administration, to aim at maintaining blood glucose levels of at least 47 mg/dl. 2,5 Previous blood glucose monitoring system (BGMS) failed to perform well in neonates; there are calls for the tightening of accuracy requirements. 5,6 A total of 300 neonates were recruited from 5 local hospitals in a multi-center clinical trial.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal hypoglycemia is the most common metabolic disorder during the neonatal period and is a recognized trigger of infantile spasms (8)(9)(10). Previous studies have found that neonatal hypoglycemia may result in hypoglycemic neurological injuries, also known as neonatal hypoglycemic brain injuries (11)(12)(13)(14)(15)(16). Udani et al examined the etiology of remote symptomatic epilepsy with onset during the first 3 years of life and observed that neonatal hypoglycemia was the most common etiology, with spasms being the most common type of seizure (14).…”
Section: Introductionmentioning
confidence: 99%
“…The cut off level which should prompt treatment remains unclear, especially in asymptomatic neonates [6].…”
Section: Introductionmentioning
confidence: 99%